Successful Management of High-Risk Pregnancy with TORCH Infection History and Chronic Hypertension - Karimah, Rumman; Fadli, Sonny; Eljatin, Dwinka Syafira; Indriastuti, Endah; Sari, Desiana Widityaning; Ridhoi, Ahmad (Journal of Medicine and Health Technology, 2024)
A 41-year-old pregnant woman of Javanese ethnicity attended the outpatient clinic of a private hospital, presented with fifth pregnancy and no living children due to a history of ectopic pregnancy, two times IUFD, and one time neonatal death. The patient also had a history of chronic hypertension and asthma. The examination showed positive IgG Toxoplasma and CMV antibody levels. The patient's blood pressure also never touched the normal limit since the beginning of pregnancy. At the end of pregnancy, she had very high blood pressure and proteinuria. According to WHO Maternal Mortality Rate (MMR) is still very high, where two of the five highest causes are infection and hypertension in pregnancy. High risk pregnancies require special attention in monitoring during pregnancy and management. In a history of bad obstetrical history it is necessary to screen for infection which can be done by antibody serology testing. A positive IgG indicates immunity to the virus, if possible it is necessary to check IgG Avidity to determine whether therapy is still needed or can rely on the immune system that has been formed. Chronic hypertension (Systolic Blood Pressure (SBP) > 140 mmHg and / or Diastolic Blood Pressure (DBP) > 90 mmHg since < 20 Weeks Gestational Age (WGA) until 42 days after delivery). First-line Labetalol and Nifedipine or second-line Methyldopa and Hydrochlorothiazide should be considered depending on the condition and gestational age. If there are signs of preeclampsia, termination should be done if possible, along with antihypertensives and anticonvulsants such as MgSO4.